EVOLUTION OF THE NATO STRATEGIC COMMUNICATION CAMPAIGN DURING THE 1999 AGGRESSION - Mitić, Aleksandar (Political Review, 2025)
Faced with internal difficulties and an unexpected intensity of resistence by the Federal Republic of Yugoslavia, NATO’s strategic communication campaign during the 1999 aggression was forced to constant adaptation. The preparatory phase of the aggression occurred in line with selective “memory politics” related to the Second World War and the conflict in Bosnia and Herzegovina, which served as motivation for the aggression given the evident violation of international law and of the UN Charter by NATO countries. This approach was in force until the first serious challenges faced by “fake news” and “collateral damage”, primarily after the bombing of a column of tractors carrying displaced Albanians near Djakovica on April 14. Faced with public pressure, key NATO officials then offered the leadership of the strategic communication campaign to Alastair Campbell, British Prime Minister Tony Blair’s “spin doctor”, with the aim of breaking growing critical public opposition, particularly within member countries. With the intensifying pressure on Belgrade to accept the conditions for the end of the bombings, the final stage of NATO’s strategic communication campaign focused on sending “terror” messages to Yugoslavia’s people, police and military. From the perspective of reaching objectives, NATO’s strategic communication campaign succeeded in overcoming the opponent. However, from the historical perspective of a quarter of a century later, the campaign was both the height of the U.S. and NATO unipolar dominance, and a trigger for transition towards a multipolar information-communication order in the light of lessons learned and adopted by the Russian Federation and the People’s Republic of China.
Keywords: NATO; 1999 aggression; Serbia; Federal Republic of Yugoslavia; strategic communication; strategic narrative